New data of the real clinical practice confirms low incidence of major bleeding when using rivaroxaban in patients with non-valvular atrial fibrillation - article Editorial (Рациональная фармакотерапия в кардиологии, 2015)
New data of the real clinical practice confirms low incidence of major bleeding when using rivaroxaban in patients with non-valvular atrial fibrillation